Effectiveness of In-service Programme on ICT for Primary Teachers Run by MCD Science Centres - Iqbal, Zafar (INDIAN EDUCATIONAL REVIEW, 2016)
To empower primary teachers of MCD Schools with ICT skills, MCD initiated ‘Shiksha’ project in collaboration with Microsoft Corporation (India) Ltd. The present study examines the effectiveness of training in ICT to the teachers in MCD Schools. The study was biphasic; a purposive sample of 400 trained teachers were chosen for comprehensive survey study in the first phase. The tools Questionnaire, Observation Schedule and Interview Schedule, were developed. In second phase, ten schools were observed and a randomly selected sample of twenty male/female teachers from the total sample of the first phase was interviewed. Even though, the results were not exciting, still it was a challenge for stakeholders to train them on ICT appropriately.